Effect of salivary urea, pH and ureolytic microflora on dental calculus formation and its correlation with periodontal status - Liberia L. D'souza; Sandeep A. Lawande; James Samuel; Maria Jose Wiseman Pinto (Elsevier, 2023)
Context: Dental calculus, formed by mineralization of plaque predisposes to the development of periodontal disease. Aim: To evaluate the influence of salivary urea and the presence of ureolytic bacteria on dental calculus formation and periodontal status in patients with good, fair and poor oral hygiene. Material and methods: An observational cross-sectional study was carried out on 135 patients, 18-60 years of age. Based on the simplified calculus index, patients were divided into three groups, good oral hygiene, fair oral hygiene and poor oral hygiene. Clinical parameters such as plaque index, gingival index, pocket probing depth and clinical attachment level and salivary pH were recorded for each subject. Saliva samples were collected to evaluate the urea levels using autoanalyzer method. Supragingival calculus samples were collected and presence and quantification of ureolytic bacteria were done by gram staining and bacterial culture and confirmed by biochemical reaction. For statistical analysis, test like Shapiro-Wilk test, Kruskal Wallis and Spearman's rho were used. Results: Increase in salivary pH was associated with increased odds of higher calculus index score (odds ratio = 2.785). There was a non-significant weak correlation between salivary urea and ureolytic bacteria in dental calculus in all the three groups (p > 0.05). Higher calculus index score was associated with increased odds of presence of ureolytic bacteria (odds ratio>1). Conclusions: Higher level of ureolytic bacteria with increasing calculus index score may breakdown the salivary urea to ammonia resulting in a ureolytic pH rise that facilitate calcium phosphate saturation leading to more calculus formation.